TI: NLRP3 Inflammasome-Dependent Pyroptosis in CNS Trauma: A Potential Therapeutic Target - Zhou, Conghui; Zheng, Jinfeng; Fan, Yunpeng; Wu, Junsong (Frontiers in Cell and Developmental Biology, 2022)
Central nervous system (CNS) trauma, including traumatic brain injury (TBI) and traumatic spinal cord injury (SCI), is characterized by high morbidity, disability, and mortality. TBI and SCI have similar pathophysiological mechanisms and are often accompanied by serious inflammatory responses. Pyroptosis, an inflammation-dependent programmed cell death, is becoming a major problem in CNS post-traumatic injury. Notably, the pyrin domain containing 3 (NLRP3) inflammasome is a key protein in the pyroptosis signaling pathway. Therefore, underlying mechanism of the NLRP3 inflammasome in the development of CNS trauma has attracted much attention. In this review, we briefly summarize the molecular mechanisms of NLRP3 inﬂammasome in pyroptosis signaling pathway, including its prime and activation. Moreover, the dynamic expression pattern, and roles of the NLRP3 inflammasome in CNS post-traumatic injury are summarized. The therapeutic applications of NLRP3 inﬂammasome activation inhibitors are also discussed.